Nasopharyngeal carriage of Staphylococcus aureus in a rural population, Sierra Leone - Lisa Maria Kleine; Emmanuel Marx Kanu; Tobias Grebe; Desmond Mohamed Sesay; Henning Loismann; Maxwell Sesay; Tom Theiler; Viktoria Rudolf; Alexander Mellmann; Laura C. Kalkman; Martin P. Grobusch; Frieder Schaumburg (International Journal of Medical Microbiology)
Background: Nasopharyngeal colonization with Staphylococcus aureus is a risk factor for subsequent infection. Isolates from colonization can therefore provide important information on virulence factors and antimicrobial resistance when data from clinical isolates are lacking. The aim of this study was to assess colonization rates, resistance patterns and selected virulence factors of S. aureus from rural Sierra Leone. Methods: Residents of randomly selected houses in Masanga, Sierra Leone were included in a cross-sectional study (8–11/2023). Participants were tested for nasopharyngeal S. aureus colonization using selective culture media. Risk factors for colonization were documented in a standardized questionnaire. Isolates were genotyped and tested for antimicrobial susceptibility and selected virulence factors (e.g. Panton-Valentine leukocidin, capsular types). Results: Of 300 participants (62.7 % females, median age: 16 years), 168 (56 %) were colonized with S. aureus-related complex; six participants carried two different S. aureus genotypes, resulting in a total number of 174 isolates. Resistance to penicillin was predominant (97.1 %, 169/174), followed by tetracycline (66.1 %, 115/174), co-trimoxazole (56.9 %, 99/174) and oxacillin (24.1 %, 42/174, all mecA-positive, mostly associated with ST8/PVL-negative). PVL gene was detected in 21.3 % of isolates (37/174) mainly associated with ST15 and ST152. Except for past use of antimicrobials (p = 0.019), no specific risk factors such as comorbidities including hemoglobin variants were associated with S. aureus nasopharyngeal colonization. Conclusion: The prevalence of methicillin-resistant and PVL-positive methicillin-susceptible S. aureus (MRSA/MSSA) is high in a rural community of asymptomatic carriers in Sierra Leone. Measures to contain the spread of MRSA, also in the community, are needed.